Analysis of GLRA1 in hereditary and sporadic hyperekplexia: a novel mutation in a family cosegregating for hyperekplexia and spastic paraparesis. Issue 5 (May 1996) - Elmslie, F V; Hutchings, S M; Spencer, V; Curtis, A; Covanis, T; Gardiner, R M; Rees, M
Abstract : Hyperekplexia is a rare condition characterised by the presence of neonatal hypertonia and an exaggerated startle response. Mutations have been described in GLRA1, the gene encoding the alpha 1 subunit of the glycine receptor, in dominant families with hyperekplexia and in a single sporadic case, thought to represent an autosomal recessive form of the disease. In this study the coding region of the GLRA1 was analysed in eight probands with hyperekplexia by restriction digest and sequencing. Two familial cases were found to possess the previously described G1192A (R271Q) mutation in exon 6. In an additional family in which hyperekplexia cosegregates with spastic paraparesis, a novel A to G transversion at nucleotide 1206 in exon 6 was detected that changes a lysine at amino acid 276 to a glutamate (K276E). In four sporadic cases no mutations were found. In addition, one familial case did not have a mutation in the coding region of the gene.